Street Vendor in Semarang: Structuring, Empowerment, and Welfare - Eko Handoyo; Iwan Hardi S (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2019)
This study aims to analyse (1) Semarang City Government policies in managing and empowering street vendors, (2) implementation of local regulations in managing and empowering street vendors, and (3) the impact of implementing policies in structuring and empowering street vendors. for their welfare. This research uses a qualitative approach and case studies and research takes place in South Batan and Penggaron. Data taken from observations, interviews, and literature studies. The results of the study were analyzed with qualitative analysis techniques from Miles & Huberman and Creswell. From the research analysis and field findings, the following results were obtained. First, the Semarang City Government manages and empowers Street Vendors by referring to regional regulation No. 11 of 2000. Second, the structuring policy carried out by the city government only focuses on the implementation of relocation and elimination of business locations. Empowerment activities managed by the government are facilitating access to capital, business facilitation assistance, trade facilities, institutional development, and limited promotion through creative product exhibitions. Third, the policies on structuring and empowering street vendors have direct and indirect impacts on the welfare of street vendors, especially in South Batan. Based on the results of the study it is recommended that the arrangement of street vendors be carried out by taking into account the interests of the community of road access and also paying attention to the future of street vendors.